Masked Warrior Emerging from a House - G.F. MacDonald Collection (1979)
Victor Mowat of the 'Ksan Performance group re-enacting the story of the warrior chief Nehl'xt or 'Nekt at 'Ksan Historical Village. The story takes place at 'Battle Hill near Gitwangak village. 'Nekt was an aggressive warrior and led many successful raids against neighbouring tribes. He is remembered and celebrated by the Gitxsan people as a powerful and great leader.